The Concept of Destiny in Between the Perspectives of Muhammad Syahrur and Robert Kane (A Critical Discourse Analysis) - Satria Tenun Syahputra; Roma Wijaya (Journal of Southeast Asian Islam and Society, 2022)
This article aims to analyze the concept of destiny from the perspective of Muhammad Syahrur and Robert Kane. The Destiny considered by Most of people to be something particular, turns out to be something that humans can still control. This opinion is undoubtedly contrary to the opinion of the majority. According to Syahrur, humans still have a significant role to play in determining their age, sustenance, and deeds, while according to Kane, humans have free will, which is not even suitable with God's provisions. This research is library research using Norman Fairclough's critical discourse analysis method, which consists of text analysis linguistically, discursive analysis or text production, and social practice analysis. This study concludes that Syahrur's opinion regarding the concept of destiny that humans can still control is obtained from an analysis of the verses of the Qur'an, which talk about age, sustenance and human charity with a linguistic approach and Kane uses a critical-logical analysis approach to the previous opinions that has existed Before. The result of the study found that according to Syahrur, the destiny is in the form of a collection of terms and conditions collected in one book, if these terms and conditions are fulfilled will cause a certain phenomenon, whether it is death, life, long or short life and so on. Meanwhile, according to Kane, human free will is like the garden of the forking path, where humans can choose which way to go without coercion from any party.